Analisis Kontroversi Aksi Cepat Tanggap Berdasarkan Perspektif Maqashid Syariah - Kusuma, Airlangga Surya; Wiryanto, Fadhli Suko; Widodo, Purwanto (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Indonesia, as the country with the largest Muslim population in the world, is also recognized as the most generous country according to the World Giving Index 2022. Islamic philanthropy in Indonesia has experienced rapid growth since the reform era, marked by an increased awareness of the importance of professional management to maximize the impact on the underprivileged. Aksi Cepat Tanggap (ACT) is one of the prominent Islamic philanthropic organizations with various initiatives such as Global Qurban and Global Wakaf, which have received positive responses from the Indonesian public. However, in 2022, ACT faced several allegations of financial misconduct, including embezzlement, misuse of donation funds from Boeing, mismanagement of waqf funds, excessive donation deductions, and money laundering. These scandals not only disrupted ACT's financial stability but also led to legal consequences for several of its executives. In Islam, the concept of Maqashid Syariah provides a framework for analyzing phenomena that may harm the Muslim community, including controversies involving ACT. This study employs a descriptive qualitative approach to examine the ACT controversies through the lens of Maqashid Syariah. Based on this analysis, as an Islamic philanthropic institution entrusted with managing ZISWAF (Zakat, Infaq, Shadaqah, and Waqf) funds, ACT should adhere to the principles of Maqashid Syariah to avoid actions that undermine the protection of intellect, life, and wealth, which are part of the Maqasid al-Khamsah. This study contributes to the literature on Islamic Economics by providing insights into the application of Maqashid Syariah in the context of Islamic philanthropy. The practical implications of this research emphasize the importance of accountability and transparency in the management of ZISWAF funds by Islamic philanthropic organizations, regulators, and the community to ensure compliance with Maqashid Syariah.